2003
DOI: 10.1046/j.1365-3164.2003.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐based veterinary dermatology: a systematic review of the pharmacotherapy of canine atopic dermatitis

Abstract: The efficacy of pharmacological interventions used to treat canine atopic dermatitis, excluding fatty acid supplementation and allergen-specific immunotherapy, was evaluated based on the systematic review of prospective clinical trials published between 1980 and 2002. Studies were compared with regard to design characteristics (randomization generation and concealment, masking, intention-to-treat analyses and quality of enrolment of study subjects), benefit (improvement in skin lesions or pruritus scores) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
194
1
12

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(209 citation statements)
references
References 42 publications
2
194
1
12
Order By: Relevance
“…In addition, studies evaluating serum histamine concentrations revealed that levels are similar [26] or lower [27] in dogs with AD compared to healthy controls, thus the role of histamine is still under debate. Interestingly, the few studies evaluating the effect of antihistamines, including H4 blockers, have failed to report a beneficial effect [28,29]. In a subset of human patients with AD, genetically inherited skin barrier defects are demonstrable and further skin barrier impairment occurs once sensitization develops and inflammation is triggered [30].…”
Section: Atopic Dermatitis: Comparative Observationsmentioning
confidence: 99%
“…In addition, studies evaluating serum histamine concentrations revealed that levels are similar [26] or lower [27] in dogs with AD compared to healthy controls, thus the role of histamine is still under debate. Interestingly, the few studies evaluating the effect of antihistamines, including H4 blockers, have failed to report a beneficial effect [28,29]. In a subset of human patients with AD, genetically inherited skin barrier defects are demonstrable and further skin barrier impairment occurs once sensitization develops and inflammation is triggered [30].…”
Section: Atopic Dermatitis: Comparative Observationsmentioning
confidence: 99%
“…Interestingly, insufficient evidence was found to support the use of antihistamines for canine AD in a systematic review. 22 This result may derive from the stringent criteria used in the review. As antihistamines are best used as adjunctive therapy, it is understandable why they would not reach sufficient efficacy to be recommended when they are tested as monotherapy.…”
Section: Long-term Approach To Chronic Casesmentioning
confidence: 99%
“…Unfortunately, very few of these have proven useful in dogs. Leukotriene receptor antagonists, 5-lipoxygenase inhibitors, and the nonsedating antihistamines have not been shown to be effective in animals (Olivry and Mueller, 2003). Medications such as pentoxifylline and misoprostol may provide some relief in a few dogs (Olivry and Mueller, 2003;.…”
Section: Pharmacological Interventionmentioning
confidence: 99%
“…Leukotriene receptor antagonists, 5-lipoxygenase inhibitors, and the nonsedating antihistamines have not been shown to be effective in animals (Olivry and Mueller, 2003). Medications such as pentoxifylline and misoprostol may provide some relief in a few dogs (Olivry and Mueller, 2003;. The newest treatments for canine AD such as the calcineurin inhibitors cyclosporin A and tacrolimus are designed to interfere with the action of interleukins and other cytokines.…”
Section: Pharmacological Interventionmentioning
confidence: 99%
See 1 more Smart Citation